Solar Cells: 3D Printer Based Slot‐Die Coater as a Lab‐to‐Fab Translation Tool for Solution‐Processed Solar Cells (Adv. Energy Mater. 4/2015). Issue 4 (February 2015) - Vak, Doojin; Hwang, Kyeongil; Faulks, Andrew; Jung, Yen‐Sook; Clark, Noel; Kim, Dong‐Yu; Wilson, Gerard J.; Watkins, Scott E.
<x xml:space="preserve">Abstract</x> In article number 1401539, Doojin Vak and co‐workers describe a new way of developing and sharing processes for the fabrication of solution‐processed solar cells by using a modified 3D printer. The printer is controlled by a text‐based standard digital protocol that can be used in any compatible printers. The results suggest a new paradigm of sharing processes between machines, labs, and eventually factories. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>